Synthesis of Potential Glycosyl Transferase Inhibitors by Thio‐Click Reactions. Issue 48 (22nd December 2021) - Debreczeni, Nóra; Bege, Miklós; Borbás, Anikó
Abstract: Leloir glycosyltransferases play an important role in many fundamental processes of living systems by catalyzing biological glycosylations. Neutral analogues of nucleotide sugars, as potential donor‐substrate inhibitors of Leloir glycosyltransferases, are of prime interest in medicinal chemistry. We report the development of S ‐linked sugar‐nucleotide analogues by replacing the α‐ O ‐pyrophosphate bridge with an electroneutral ethyl or propyl linker by radical mediated hydrothiolation of 2‐substituted glycals and olefinic nucleoside analogues. UDP‐glucose and UDP‐GlcNAc analogues were assembled from 2‐substituted glycals, 1, 2‐ethanedithiols and uridine 4'‐exomethylene derivative by two subsequent thio‐click reactions. Morpholino type mimetics of UDP‐, GDP‐ and CMP‐sugars were constructed by photoinitiated additions of 1‐thiosugars (Glc, GlcNAc, Gal, Man) and 2‐thio‐Neu5Ac onto N ‐allyl morpholinos. Abstract : Thio‐linked analogues of UDP‐sugars, GDP‐mannose and CMP sialic acid that contain an electroneutral alkyl chain to replace the native α‐ O ‐pyrophosphate or ‐phosphate bond were synthesized through radical mediated thiol‐ene coupling reactions. The 1, 2‐cis‐α‐1‐thiosugars obtained by hydrothiolation of 2‐substituted glycals were coupled to nucleoside 4'‐exomethylenes or N ‐allyl‐morpholinos.